He Obligation Of The Land Deed Making Officer To The Authenticity Of The Deed Made As Evidenc - Buldan Firanda, Syahril Izha Ferri (Universitas Islam Malang, 2023)
Abstract : The making of an authentic deed is only determined by law, while the official who can make it inevitable to have the same weight must also be determined by laws or regulations at the same level as the law, so that only Notaries are authorized to make authentic deeds while from the other side PPAT also has the authority to make authentic deeds, therefore there are problems with the authority of PPAT in making authentic deeds where the phrase is only determined by law contrary to the tentaun of Government Regulation Number 24 of 1997 concerning Land Registration and Regulation of the Head of the National Land Agency Number 8 of 2012 concerning Amendments to the Regulation of the Minister of Agrarian State/Head of the National Land Agency Number 3 of 1997 concerning Provisions for the Implementation of Government Regulation Number 24 of 1997 concerning Land Registration, which in such regulation is not a law only a regulation under it.Based on this background, this paper raises the following problem formulation: 1. What is the obligation of the Land Deed Making Officer to ensure the authenticity of the Land Deed he made? 2. What is the validity of the evidentiary power made by the Land Deed Making Officer in realizing written evidence? This research is a type of normative juridical research. Normative juridical research is research that examines laws and regulations in a coherent legal system and unwritten legal values that live in society. The type of approach used in research is as an effort in the framework of research activities to establish relationships with those studied or methods to achieve an understanding of the research problem. This research uses a Statutory approach and a Conceptual Approach, where with these approaches researchers will obtain information from various aspects related to the authenticity of the PPAT deed made as evidence. Based on the results of research conducted with literature studies, broadly speaking the results of this research can be concluded as follows: That the obligation of PPAT to ensure the authenticity of the land deed it makes is based on first checking at the Land Office regarding the suitability of the certificate of land rights or Ownership Rights to the Flats Unit concerned with the lists at the local Land Office by showing the original certificate. And PPAT is obliged to check the completeness file and witnesses by reading the deed to the parties concerned and providing an explanation of the content and purpose of making the deed, and the registration procedure that must be carried out subsequently in accordance with applicable regulations. That the validity of the evidentiary power made by the PPAT in realizing written evidence is explained in Article 1871 of the Civil Code by giving and delivering the signing to the official who made it and determined from concrete matters, namely from the suitability of the information given by the parties when facing the PPAT and the propriety of a PPAT in exercising its authority in making authentic deeds by following the provisions contained in the Government Regulation Number 37 of 1998 concerning Regulations for the Position of Land Deed Making Officers, and Government Regulation Number 24 of 2016 concerning Amendments to the Regulations for the Position of Land Deed Making Officials.Keywords : Authentic Deed, Evidence, PPAT